Genetic variability for responses to short‐ and long‐term salt stress in vegetative sunflower plants - Ceccoli, Gabriel (2012)
Sunflower (Helianthus annuus L.) has been rated as moderately salt‐resistant, and variability for salt resistance has been detected within this crop. However, variability in salt‐resistance mechanisms has not been assessed. Osmotic tolerance, the relation of salt resistance with whole‐plant Na+ and K+ distribution and tissue Na+ tolerance were investigated in several sunflower inbred lines. Plants were grown under controlled conditions, in pots with sand and perlite irrigated with salinized (NaCl, –0.65 MPa) nutrient solution. Osmotic tolerance was assessed from the initial effects of the salt treatment on plant elongation in eleven sunflower lines. Long‐term salinity responses were evaluated in four of those lines, by assessing whole‐plant growth. A principal components analysis (PCA) was run on relative‐to‐control growth data, and this information was used to establish a relative resistance ranking, which indicated lines HAR2 > HAR1 > HA64 > HAR5. Osmotic tolerance was observed in HA64 and HAR2. The lines showed different degrees of Na+ accumulation, it was very low in some of them, but relative salt resistance was not associated to this trait. Tissue Na+ tolerance was deduced by comparing the percentage of dead leaves as a function of leaf blade Na+ accumulation, and it was higher in HAR1 than in the rest. These results indicate that variability for salt‐resistance mechanisms exists in sunflower. Osmotic tolerance and tissue Na+ tolerance were detected in different lines, highlighting that such variability may be exploited for increasing salt resistance in this crop.